2007
DOI: 10.3390/i8070618
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Effects on Phenolic Content, Lipid and Protein Oxidation and Scavenger Ability of Soybean Seeds

Abstract: Abstract:The effect of medium doses of γ-irradiation (1-10 kGy) on total phenolic and tannin contents, lipid peroxidation, protein oxidation intensity and soluble protein content of soybean seeds, (genotype Ana), was investigated. Screening for antioxidant ability was performed using FRAP and DPPH methods. Total phenolic and tannin contents and DPPH scavenger activity were increased, while protein oxidation intensity was decreased by applied doses of γ-irradiation. Gamma irradiation provoked insignificant chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 20 publications
7
54
3
Order By: Relevance
“…The initial content of soluble protein for cultivar NA 5909 RG was 104.26 mg.g -1 , being similar for cultivar Benso1RR, with a content of 110.11 mg.g -1 , being close to the value found by Stajner et al (2007) who have observed 95 mg.g -1 of soluble protein in soybean seeds, and the authors have not observed any changes when different γ radiation dosages were applied to the seeds, and no difference was observed in the soluble protein contents of this study among the seeds from desiccated plants regarding their control (Table 1).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The initial content of soluble protein for cultivar NA 5909 RG was 104.26 mg.g -1 , being similar for cultivar Benso1RR, with a content of 110.11 mg.g -1 , being close to the value found by Stajner et al (2007) who have observed 95 mg.g -1 of soluble protein in soybean seeds, and the authors have not observed any changes when different γ radiation dosages were applied to the seeds, and no difference was observed in the soluble protein contents of this study among the seeds from desiccated plants regarding their control (Table 1).…”
Section: Resultssupporting
confidence: 66%
“…In 48 h of soaking, seeds from desiccated plants reached almost the same percentage (100%) of root protrusion compared to their controls (Figure 2), indicating the start of phase III. Similar data for soybeans and beans seeds have been observed, and phase III occurs at 40 hours of soaking for soybeans seeds and at 30 h for beans seeds (Teulat-Merah et al, 2011;Cheng et al, 2009).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…It were shown that gamma radiation can increases (Moussaid et al, 2000, Mechi et al 2005, Miranda et al 2006, Bhat et al 2007, Stajner et al 2007, decreases (Villavicencio et al 2000;Brigide & Canniatti-Brazaca, 2006, Toledo et al, 2007 or unchanged levels of total phenols and/or tannins (Koseki et al, 2002) in plant extracts from some plants, and raw or cooked, which had considerable percentage of moisture, favoring the indirect effects of radiation (Mechi et al, 2005, Brigid & Canniatti-Brazaca, 2006. These studies are unprecedented as the characterization of dry vegetable matter, which dominates the interaction of gamma radiation from the direct effect.…”
Section: Resultsmentioning
confidence: 99%
“…•-) radicals that are generated by irradiation could modify the molecular properties of the proteins and lipids, causing oxidative modifications of the proteins and lipid peroxidation (LP) [7,8]. Chemical changes of the proteins that are caused by γ-irradiation include fragmentation, cross-linking, aggregation and oxidation resulting from oxygen radicals that are generated in the radiolysis of water [9].…”
Section: Introductionmentioning
confidence: 99%